Pentingnya Pengenalan Keragaman Budaya pada Anak Sekolah Dasar untuk Menumbuhkan Sikap Toleransi di Era Globalisasi - Nisrina, Najwa Adistia; Hurulaynizarqa; Indriani, Tania; Wahyuningsih, Yona (Indo-MathEdu Intellectuals Journal, 2025)
Rapid globalization has had a major impact on social and cultural changes that can weaken elementary school students' tolerance of diversity. However, as a multicultural nation, Indonesia needs a generation that is able to appreciate differences from an early age. This study aims to analyze the effectiveness of introducing cultural diversity in fostering tolerance among elementary school students in the era of globalization. The research method uses a Systematic Literature Review (SLR) approach by examining ten relevant articles based on predetermined inclusion and exclusion criteria. The results of the study show that diversity-based learning can improve students' understanding of national identity and foster mutual respect in social interactions. The role of teachers, family support, and the use of digital learning media also strengthen the internalization of tolerance values in students. Thus, introducing cultural diversity is an important strategy in shaping a tolerant character in the younger generation facing global challenges.